FUNGSI LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI KELURAHAN SETERIO KECAMATAN BANYUASIN III KABUPATEN BANYUASIN - Sugitok, Sugitok (Jurnal Ilmiah Administrasi Dan Sosial, 2022)
The Kelurahan Community Empowerment Institution (LPMK) is an institution or forum formed on the initiative of the community as a Lurah partner in accommodating and realizing the aspirations and needs of the community in the field of development. The sub- district community empowerment institution is based in the sub-district as a lurah partner in the field of development and community empowerment. The tasks of the Kelurahan community empowerment institution are to prepare development plans in a participatory manner, mobilize community self-help, implement and supervise development control. This is the main priority of the institution.The  research  objective  was  to  analyze  the  function  of  the  Kelurahan  Community Empowerment Institution in increasing community participation in Seterio Kelurahan, Banyuasin III District, Banyuasin Regency. To find out the factors that are driving and inhibiting the function of Village Community Empowerment Institutions in increasing Community Participation in Seterio Village, Banyuasin III District, Banyuasin Regency. The method used is a qualitative method, data collection techniques are carried out by observation, interviews with parties involved in becoming research informants, literature studies, documentation, and data analysis techniques.The results showed that the function of Kelurahan Community Empowerment Institutions in increasing Community Participation in Seterio Kelurahan, Banyuasin District, Banyuasin Regency had not been carried out optimally because LPMK had not captured the aspirations of the community, further development planning had not been carried out and  all  mutual  cooperation  activities  were  community  initiatives  not  from  LPMK, resulting in Community empowerment is not implemented properly. Factors driving and inhibiting the Function of Kelurahan Community Empowerment Institutions in Increasing Community Participation in Seterio Kelurahan, Banyuasin District, Banyuasin Regency The driving factor is strengthening the function of RT which causes faster service. While the inhibiting factor is that the socialization of LPMK activities has not been maximized so that the community does not know that there is an LPMK organization in Seterio Village. Keywords: LPMK, Participation